Molecular Regulation of Arterial Aneurysms: Role of Actin Dynamics and microRNAs in Vascular Smooth Muscle - Alajbegovic, Azra; Holmberg, Johan; Albinsson, Sebastian (Frontiers in Physiology, 2017)
Aortic aneurysms are defined as an irreversible increase in arterial diameter by more than 50% relative to the normal vessel diameter. The incidence of aneurysm rupture is about 10 in 100 000 persons per year and ruptured arterial aneurysms inevitably results in serious complications, which are fatal in about 40% of cases. There is also a hereditary component of the disease and dilation of the ascending thoracic aorta is often associated with congenital heart disease such as bicuspid aortic valves (BAV). Furthermore, specific mutations that have been linked to aneurysm affect polymerization of actin filaments. Polymerization of actin is important to maintain a contractile phenotype of smooth muscle cells enabling these cells to resist mechanical stress on the vascular wall caused by the blood pressure according to the law of Laplace. Interestingly, polymerization of actin also promotes smooth muscle specific gene expression via the transcriptional co-activator MRTF, which is translocated to the nucleus when released from monomeric actin. In addition to genes encoding for proteins involved in the contractile machinery, recent studies have revealed that several non-coding microRNAs (miRNAs) are regulated by this mechanism. The importance of these miRNAs for aneurysm development is only beginning to be understood. This review will summarize our current understanding about the influence of smooth muscle miRNAs and actin polymerization for the development of arterial aneurysms.